A SURVEY OF URINALYSIS IN HAZARA POPULATION - Khan, Mir Hassan; Akbar, Mujahid; Khan, Jahangir A.; Shah, S. Humayun; Ullah, Zakir (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT Urine of 11600 subjects of Hazara Division were analysed between October, 1989 and November, 1990. Age range was 10-70 years. Physical, chemical and microscopic composition were observed. Most of the samples were pale yellow, had a volume of 1- 1.5 1/24 hrs and few of them were turbid. pH and specific gravity were found in the range of 5-8 and 1.018-1.026 respectively. 369 cases of albuminuria, 205 cases of glycosuria and 93 cases of ketonuria were detected. Jaundice was detected only in few individuals. The abnormal leukocytes, RBC, Epithelial cells, Amorphous urates, Calcium oxalate crystals and Uric acid crystals were found in less than 12% subjects. Different types of casts observed were negligible.